Determinant of Incompliance Medication People with Tuberculosis Disease - Chilyatiz Zahroh1 , Nur Ainiyah1 , Nurus Saadah1 , Novita Nur Aini1 , I Ketut Sudiana2 , Ah. Yusuf3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Indonesian Tuberculosis (Tb) case is the highest third rank in the world. It is caused by disobediencein therapy. Three factors affect medication compliance include predisposing, reinforcing and enablingfactors. This research aims to analyzed factors that affects medication compliance in Indonesian Tbpatients. The study was analytical research. The population were 119 Tb patients in Surabaya Health carecenter, Indonesia. Simple random sampling technique was used to take sample, consist of 93 respondents.The variables of this study were predisposing factors, reinforcing factors and enabling factors. The datawas collected with questionnaires and analyzed with chi square test. The study showed that all factorsrelated to incompliance medication people with Tb, namely predisposing factors: knowledge, attitude,belief (p=0.000), trust (p=0.013, and values (p=0.001); reinforcing factors: family support (p=0.034) andhealthcare personnel support (p=0.022); and enabling factors: healthcare facility (p=0.000) and physicalenvironment (p=.000). The determinants of incompliance medication people with Tb include predisposingfactors (knowledge, attitudes, beliefs, trust and values); reinforcing factors (family and healthcare personnelsupport); and enabling factors (healthcare facility and environment). Tackling incompliance medication onTb should involve private sector, family sector, society/healthcare sector and government sector.